Vav2 is required for Netrin‐1 receptor‐class‐specific spinal motor axon guidance. Issue 3 (13th August 2021) - Tsou, Yi‐Syue; Wang, Chih‐Yang; Chang, Ming‐Yuan; Hsu, Tsung‐I; Wu, Meng‐Ting; Wu, Yi‐Hsin; Tsai, Wan‐Ling; Chuang, Jian‐Ying; Kao, Tzu‐Jen
Abstract: Background: Proper guidance of neuronal axons to their targets is required to assemble neural circuits during the development of the nervous system. However, the mechanism by which the guidance of axonal growth cones is regulated by specific intermediaries activated by receptor signaling pathways to mediate cytoskeleton dynamics is unclear. Vav protein members have been proposed to mediate this process, prompting us to investigate their role in the limb selection of the axon trajectory of spinal lateral motor column (LMC) neurons. Results: We found Vav2 and Vav3 expression in LMC neurons when motor axons grew into the limb. Vav2, but not Vav3, loss‐of‐function perturbed LMC pathfinding, while Vav2 gain‐of‐function exhibited the opposite effects, demonstrating that Vav2 plays an important role in motor axon growth. Vav2 knockdown also attenuated the redirectional phenotype of LMC axons induced by Dcc, but not EphA4, in vivo and lateral LMC neurite growth preference to Netrin‐1 in vitro. This study showed that Vav2 knockdown and ectopic nonphosphorylable Vav2 mutant expression abolished the Src‐induced stronger growth preference of lateral LMC neurites to Netrin‐1, suggesting that Vav2 is downstream of Src in this context. Conclusions: Vav2 is essential for Netrin‐1‐regulated LMC motor axon pathfinding through Src interaction. Key Findings: Spinal cord, motor neuron, axon guidance.